2017
DOI: 10.1021/acs.accounts.7b00224
|View full text |Cite
|
Sign up to set email alerts
|

Interparticle Reactions: An Emerging Direction in Nanomaterials Chemistry

Abstract: Nanoparticles exhibit a rich variety in terms of structure, composition, and properties. However, reactions between them remain largely unexplored. In this Account, we discuss an emerging aspect of nanomaterials chemistry, namely, interparticle reactions in solution phase, similar to reactions between molecules, involving atomically precise noble metal clusters. A brief historical account of the developments, starting from the bare, gas phase clusters, which led to the synthesis of atomically precise monolayer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
121
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(123 citation statements)
references
References 59 publications
2
121
0
Order By: Relevance
“…Recently, reactions between clusters in solution phase were also reported. [59][60][61][62][63][64] These reactions invariably involve the metal atoms and ligands in the staple or mount motifs of these clusters. [65][66][67][68] Dynamic nature of the staple motifs or mounts [69][70][71][72][73][74] and reactions of these 4 clusters have been studied, mostly in the solution phase.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, reactions between clusters in solution phase were also reported. [59][60][61][62][63][64] These reactions invariably involve the metal atoms and ligands in the staple or mount motifs of these clusters. [65][66][67][68] Dynamic nature of the staple motifs or mounts [69][70][71][72][73][74] and reactions of these 4 clusters have been studied, mostly in the solution phase.…”
Section: Introductionmentioning
confidence: 99%
“…In this review, we expect to highlight part of the contribution from the Latin American region in the field of superatoms and related clusters, which is particularly focused in the area of gold chemistry. In the same venue, the reader is warned that only part of the global literature is covered in the current review, where for a more concise bibliography the reader requires more extensive literature reviews . It is important to note that available computational resources are able to count on the experimentally available data in good faith, allowing for further understanding, prediction and proper design of novel undiscovered structures.…”
Section: Introductionmentioning
confidence: 90%
“…In the same venue, the reader is warned that only part of the global literature is covered in the current review, where for a more concise bibliography the reader requires more extensive literature reviews. [1,25,[37][38][39] It is important to note that available computational resources are able to count on the experimentally available data in good faith, allowing for further understanding, prediction and proper design of novel undiscovered structures. In this sense, relativistic density-functional-theory (DFT) appears to be valuable tool, since it enables the study to be carried out with a moderate computational effort.…”
mentioning
confidence: 99%
“…Inter-cluster reactions are an emerging area in the field of NCs 107 . Krishnadas et al demonstrated the reaction between Au 25 (FTP) 18 and Ag 44 (FTP) 30 NCs, which produces a mixture of alloy clusters in solution 108, 109 .…”
Section: Reactions Between Nanoparticlesmentioning
confidence: 99%
“…Salassa et al used MALDI MS and NMR spectroscopy to show that monolayers of clusters are dynamic in nature, and inter-cluster ligand exchanges can occur during collision between the NCs 111 . Using isotopically pure silver clusters made of 107 Ag and 109 Ag, Chakraborty et al studied rapid isotopic exchange in silver clusters by HR ESI MS and found that the solution-state exchange dynamics of the clusters is similar to that occurring in water (H 2 O + D 2 O = 2HDO) 112 .…”
Section: Reactions Between Nanoparticlesmentioning
confidence: 99%